Concurrent validity of electronic von Frey as an assessment tool for burn associated pain. Issue 6 (September 2020) - Diógenes, Ana Kely de Loyola; Fechine, Francisco Vagnaldo; Costa, Bruno Almeida; Soares, Maria Flaviane Araújo do Nascimento; Rocha, Marina Becker Sales; Moraes Filho, Manoel Odorico de; Lima Júnior, Edmar Maciel; Vale, Mariana Lima
Highlights: Most available burn pain evaluation methods are qualitative and highly subjective. Electronic von Frey evaluates pain based on mechanical sensory thresholds measures. Electronic von Frey and Visual Analog Scale have a significant positive correlation. Electronic von Frey needs special equipment and training but is clinically feasible. The discussed tool can be used for objective burn pain assessment in clinical trials. Abstract: An important challenge in pain assessment is the inability of an evaluator to corroborate, using objective signs or indicators, the subjective pain report of a patient. In this scenario, the Electronic von Frey (EVF) anaesthesiometer rises as a valuable Quantitative Sensory Testing modality for pain evaluation. Although EVF showed good reproducibility when applied to healthy areas in humans, its use for evaluation of burn-related pain threshold has not yet been validated. The present study demonstrated the concurrent validity of EVF by determining its correlation with the traditionally used Visual Analog Scale (VAS). EVF was compared to VAS through pain measurements obtained from 44 patients with superficial partial thickness burns treated with silver sulfadiazine. A very good and significant positive correlation between both methods was detected. Baseline clinical and demographic parameters did not significantly affect the association between EVF and VAS. Additionally, EVF had significant and moderate positive correlation with the amount of analgesic used and with the Burns Specific Pain Anxiety Scale scores. Regular pain assessment is essential for the establishment of an appropriate treatment plan; thus, it is critical that we continue to refine our pain assessment skills to avoid chronic pain and psychological trauma in burn patients.